Microglial phenotypes in Parkinson’s disease and animal models of the disease - Joers, Valerie (Prog Neurobiol, 2016)
Over the last decade the important concept has emerged that microglia, similar to other tissue macrophages, assume different phenotypes and serve several effector functions, generating the theory that activated microglia can be organized by their pro-inflammatory or anti-inflammatory and repairing functions. Importantly, microglia exist in a heterogenous population and their phenotypes are not permanently polarized into two categories; they exist along a continuum where they acquire different profiles based on their local environment. In Parkinson’s disease (PD), neuroinflammation and microglia activation are considered neuropathological hallmarks, however their precise role in relation to disease progression is not clear, yet represent a critical challenge in the search of disease-modifying strategies. This review will critically address current knowledge on the activation states of microglia as well as microglial phenotypes found in PD and in animal models of PD, focusing on the expression of surface molecules as well as pro-inflammatory and anti-inflammatory cytokine production during the disease process. While human studies have reported an elevation of both pro- or anti-inflammatory markers in the serum and CSF of PD patients, animal models have provided insights on dynamic changes of microglia phenotypes in relation to disease progression especially prior to the development of motor deficits. We also review recent evidence of malfunction at multiple steps of NFκB signaling that may have a causal interrelationship with pathological microglia activation in animal models of PD. Finally, we discuss the immune-modifying strategies that have been explored regarding mechanisms of chronic microglial activation.